SISTEMATIK REVIEW EFEKTIVITAS DAN MANFAAT PRENATAL YOGA TERHADAP KELUHAN NYERI PUNGGUNG PADA IBU HAMIL - Mardliyana, Nova Elok (Sinar : Jurnal Kebidanan, 2023)
Objective: Back pain is one of the discomforts experienced by pregnant women, usually occurring in the lumbosacral area, namely in the size of the waist and pelvis. One way to reduce this discomfort is to do physical activity during pregnancy, including prenatal yoga or pregnancy yoga. Yoga in pregnancy involves particular movements and techniques beneficial for pregnant women, such as relaxation techniques, which can reduce the discomfort arising from body changes during pregnancy. This research aims to determine the effectiveness and benefits of prenatal yoga or pregnancy exercises for back pain in pregnant women.   Methods:  The research method used is a systematic review. Research sources were obtained from searching scientific articles via the internet with the Google Scholar database from 2012-2023 using PICO "pregnant women and prenatal yoga and back pain," resulting in 1,500 pieces after identification, screening, and eligibility through inclusion and exclusion criteria. Five articles that fit the inclusion criteria.   Results: The five journal articles discuss the benefits and effectiveness of complementary therapy, namely prenatal yoga or pregnancy yoga, to reduce the intensity of back pain experienced by pregnant women. One article compares the point of pregnancy exercise and pregnancy yoga, proving that pregnancy yoga is more effective in reducing back pain than pregnancy exercise. Conclusion: The conclusion based on this research shows that prenatal yoga or pregnancy yoga is effective and proven to help overcome or reduce the intensity of back pain in pregnant women